Pengaruh Knowledge Sharing Terhadap Kinerja Karyawan - Putri, Gina Annisa; Raharso, Sri (Jurnal Riset Bisnis dan Investasi, 2015)
This study aimed to analyze the influence of knowledge sharing on the job performance of Bank Indonesia Representative Office of West Java Province. The purpose of this study was to determine the level of knowledge sharing and job performance, and the influence of knowledge sharing on the job performance at Bank Indonesia Representative Office of West Java Province. Knowledge sharing variables measured by knowledge donating and knowledge collecting (de Vries et al, 2006), while the job performance variable is measured by job role, career role, innovator role, team role and organizational role (Welbourne et al, 1998), Samples were employees of Bank Indonesia Representative Office of West Java province, amounting to 103 people. Data collection techniques in this study were the observation and questionnaires. Data analysis technique used in this study is a simple linear regression. The data is processed by using SPSS (Statistical Program for Social Science for Window) version 20.0. The results showed that knowledge sharing has a positive and significant influence on job performance. Based on the value of R Square of 0,139. Which means that 13,9% of job performance (Y) can be explained by knowledge sharing (X). While the remaining 86,1% can be explained by other variables not examined in this study.